Influence Of Health Education On Knowledge And Attitude About The Hazards Of Smoking - Irma Hartati; Sari Tiara Putri (International Journal of Educational Research & Social Sciences, 2021)
Smoking activity among youth or high school students is not a new thing. For high school students, smoking is usually consumed by men, but at this time smoking is not only consumed by men, women have also consumed it. Therefore, it is necessary to make prevention efforts both in the home, school and community environment. One of the efforts made is outreach activities or health education in the school environment to provide information and knowledge to the target, especially for students who abuse it and raise their awareness about the dangers of smoking. This study aims to determine the effect of providing health education on knowledge and attitudes about the dangers of smoking in SMA Ungul CND Langsa. The design of this study used a quasi-experimental type using a one group pretest-posttest design. This study uses primary data that is processed univariately. The data are presented in the form of frequency distribution tables, cross tables and narratives. The instrument used in this research is a questionnaire which was developed based on the research variables. The number of samples in this study were 20 respondents with purposive sampling technique. The results showed that before being given the intervention the knowledge of the research subjects showed a score of 11, while after being given the intervention the score of knowledge increased to 12.5 and before being given the intervention the attitude of the research subjects showed a score of 50, while after being given the intervention the score of attitudes increased to 64. This study also concluded that there was an effect of providing health education on adolescent knowledge about the dangers of smoking with a p-value of 0.000 (p<0.05). Researchers suggest to SMA CND Langsa Superior, in order to create a health counseling program in collaboration with local health agencies. The program will help students obtain correct and accurate information about specific health about the dangers of smoking.